Analisis Yuridis Normatif Kebijakan Publik Penanggulangan Prostitusi - Jakobus Anakletus Rahajaan; Sarifa Niapele (Public Policy : Jurnal Aplikasi Kebijakan Publik dan Bisnis, 2023)
Prostitution is a serious problem because it has a very broad impact on the joints of people's lives. This study aims to analyze thequality of public policies in tackling prostitution in the city of Ambon. This research is a type of normative legal research, using the Satute Approach and Conceptual Approach. The results of this study found that in the era of autonomization, the policy of overcoming prostitution in the city of Ambon, namely Ambon City By law Number 3 of 2017 concerning Peace and Public Order, is still low or poor in quality. This weakness greatly affects the professionalism of the city government apparatus and its stakeholders in carrying out their duties and functions in countering prostitution, resulting in a low-quality community legal culture. The Law function as a tool of engineering has not been well realized. Public policymakers in Ambon City need to evaluate their performance and make better public policies. Public policy must be in accordance with the principles of forming good laws and regulations so that they have good quality as a juridical foundation that provides legal certainty, legal expediency and legal justice to the community.